2011
DOI: 10.1063/1.3621353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cap layer thickness on the perpendicular magnetic anisotropy in top MgO/CoFeB/Ta structures

Abstract: The perpendicular magnetic anisotropy of a series of top MgO/CoFeB/Ta layers is studied. Similar to the bottom Ta/CoFeB/MgO structure, the critical thickness of CoFeB is limited in a range of 1.1–1.7 nm. However, the cap layer shows much sensitive effect. Not only the type of material is crucial, but the thickness of the cap layer also affects the magnetic anisotropy. The perpendicular anisotropy of a 1.2 nm-thick CoFeB can only exist with the capping Ta thickness less than 2 nm. The magnetic characterizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…It was experimentally found that Ta layer was very crucial for obtaining PMA [7,[10][11][12]. Some argued that Ta could diffuse into the interface of CoFeB/MgO to destroy the orbital hybridization, which is harmful for achieving PMA [7,10,12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was experimentally found that Ta layer was very crucial for obtaining PMA [7,[10][11][12]. Some argued that Ta could diffuse into the interface of CoFeB/MgO to destroy the orbital hybridization, which is harmful for achieving PMA [7,10,12].…”
Section: Introductionmentioning
confidence: 98%
“…The system of CoFeB/MgO was one of the best materials for low magnetostriction and high MR. PMA has been achieved through adjusting the thickness and composition of CoFeB layer due to the proper orbital hybridization of Co-O or Fe-O [2,7,[10][11][12]. It was experimentally found that Ta layer was very crucial for obtaining PMA [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Another essential parameter involved is the thickness of capping or buffer layer, specifically the "window effect", which means that PMA may disappear due to either too thick or too thin nonmagnetic film. Cheng et al [43] measured the magnetic properties in MgO/CoFe/Ta structure and concluded that the window margin is 1.1-1.7 nm in top stack. As for W/CoFe/MgO structure, the effect occurs in bottom stack rather than top stack, showing a maximum anisotropy field of 5.9 kOe with 5.6 nm W film [49].…”
Section: Capping or Buffer Layer Materialsmentioning
confidence: 99%
“…Apart from CoFeB/MgO interface, the buffer or capping layer has been recently verified the significance to induce interfacial PMA, both by experiment and first-principles calculation [43][44][45][46][47][48][49][50]. PMA based MTJ with Ta/CoFe/MgO structure is classic, whereas the annealing temperature must be strictly controlled, for the Ta, Co, and Fe diffusion at Ta/CoFeB interface is intensified when temperature arises above 300 °C, and the diffusion induced magnetic dead layer degrades PMA dramatically.…”
Section: Capping or Buffer Layer Materialsmentioning
confidence: 99%
“…Particularly, S. Ikeda et al obtained Ta/FeCoB/MgO/FeCoB/Ta perpendicular magnetic tunnel junctions with high TMR ratio (over 120%), high thermal stability at a dimension of 40 nm diameter, and a low switching current of 49 μA [19], revealing a promising building block for future high-density memories. After that, lots of experiments based on Fe 1 −x Cox/MgO magnetic tunnel junctions have been performed to explore the influence of growth regulation, electric field, Fe-Co proportion, and so on [20][21][22][23]. Though it has been proved by experiments that Fe-rich Fe1−xCoxB/MgO structures have larger PMA than their Co-rich counterparts, there is short of theoretical guidance for optimizing Fe-Co proportion, and the inherent origin of PMA in Fe1−xCoxB/MgO is still unclear.…”
Section: Introductionmentioning
confidence: 99%